A novel approach for the production of a non‐alcohol beer (≤0.5% abv) by a combination of limited fermentation and vacuum distillation. Issue 4 (12th October 2017) - Jiang, Zhumao; Yang, Baoyu; Liu, Xiao; Zhang, Song; Shan, Jing; Liu, Jie; Wang, Xiaoran
Abstract : Despite the increasing demand, the production of non‐alcohol beers is still limited by unsatisfactory or artificial flavour and taste. In this study, a novel approach to producing non‐alcohol beer is presented, in which the alcohol‐reducing techniques, limited fermentation and vacuum distillation were combined. Starting from barley and wheat malts, wort with a low level of fermentable sugars was prepared by infusion mashing and lautering. Limited fermentation was carried out by Saccharomycodes ludwigii at 18°C. When the level of fermentable sugar was reduced by 25%, the fermented wort was quickly cooled from 18 to 0°C and held at that temperature for two days. The young beer was obtained after degassing and removal of yeast and was then subjected to vacuum distillation at 0.06 MPa to remove the alcohol. The concentrated extract is suitable for storage and transportation. The final product of non‐alcohol beer was obtained by dilution with deoxygenated water and carbonation with 6.0 g/L CO2, followed by addition of 8–12% of regular beer and equilibration for 2–3 days to develop normal beer aroma. The results showed that the non‐alcohol beer had several favourable properties, including the alcohol level of <0.5% ( v /v), colour 7.0 (EBC), thiobarbituric acid value of 1.05 and ratio of alcohols to esters of 1.08. Compared with other methods for the production of non‐alcohol beer, this novel approach produced a favourable alternative to regular beers with similar flavour characteristics and satisfactory stability. Copyright © 2017 The Institute of Brewing & Distilling